A desistência da carreira docente na rede Estadual Paulista: precarização, precariedade e frustração - Moreira, Gláucia Lucas Ramiros (2020)
The goal of this research is to identify the reasons which lead public teachers from the 2010 and 2013 tenures of the State of São Paulo to resign from their positions and give up their teaching career altogether. Based on previous research and preliminary and sequential inquiries on the subject, this work’s hypothesis is that teachers were released from their positions due to various elements related to: precarious infrastructure and work conditions; the predominance of a productivist perspective; and to the pervasive managerial logic in the school context. According to the assumptions and procedures of qualitative research, documentary data were collected and eight individual semi-structured interviews were conducted with teachers who were exonerated from their positions in the São Paulo state network. The data obtained in the interviews, along with documentary data, were systematized, categorized and interpreted with the use of “content analysis” by Bardin (1979), which provided a joint and contextualized analysis. As a result, the main factors influencing the dismissal at the request of teachers were identified, namely: the education system, the school (dis)organization and the daily work environment, permeated by tensions, conflicts, violence and indiscipline situations, as well as by, often averse, managerial practices to teaching identity and pedagogical expectations; the process of precarious work and the situation of objective precariousness; the subjective precariousness and the feelings derived from it; and the fact that teachers felt ill because of their work. Considering the content of the interviews, it was found that, despite remuneration being an important factor, the frustration and negative feelings resulting from the lack of recognition and strangeness towards work, as well as the lack of prestige and the “precariation-precariousness” duo, had a strong influence on teacher’s decision to resign.